RETHINKING THE “BARCELONA MODEL”: MULTIPLE REPRESENTATIONS OF THE CITY - Fernandes, Ana Maria Viera; Paes, Maria Tereza Duarte (Geo UERJ, 2021)
Introduction: this paper analyzes the renovation that took place in Barcelona, Spain, between the 1980s and 1990s, when significant transformations were made to host the 1992 Olympics, and takes this urbanism of the “Barcelona Model” as a reference to reflect on the process of contemporary urban regeneration from the implementation of policies of image and refunctionalization of tourism. Objective: after recovering the historical process of such interventions that initially sought to correct the problems inherited from Francoism, such as densities and scarcity of public spaces, equipment, services and housing, we seek to present the strategies of urban planning to introduce the city to the global market, making it one of the main tourist destinations in Europe, with strong socio-spatial contradictions between tourist uses and the uses of the city by local residents. Methods: the results of this research were based on literature review, documents analysis and fieldwork with the conduction of in-depth interviews with important agents representing the analysed process. Results: the demystification of the “Barcelona Model”, based on its presentation and critical analysis, confirms that urban “models” can only serve as inspiration, review and criticism, but cannot be replicated as recipes in cities with different influences. Conclusion: the uncontrolled excess of tourists in the city revealed the need for new instruments to regulate the sector regarding the concentration in tourist spots and the quality of life of the local residents, mainly in relation to real estate speculation, the cost of living, and the cultural impacts of the so-called ’overtourism’.